Being acted: dramaturgical masochism in Henry James's 'Nona Vincent'. Issue 1 (2nd January 2021) - Jarcho, Julia
ABSTRACT: This article offers a new account of masochism, retheorising it in terms of both gender and artistic practice through a reading of Henry James's 'Nona Vincent' (1892). In this story, theatre structures a mode of pleasure that explodes the gendered division of artistic labour whereby women inspire and men 'do'. This feminising fantasy of authorship responds to the scandals spawned by performances of Ibsen's 'women's plays' in London.